2000
DOI: 10.1128/jcm.38.6.2330-2333.2000
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Bordetella holmesii from Patients with Pertussis-Like Symptoms: Use of Pulsed-Field Gel Electrophoresis To Characterize Circulating Strains

Abstract: A 4-year retrospective study showing that we isolated Bordetella holmesii, but not Bordetella pertussis, from patients with pertussis-like symptoms was performed. From 1995 through 1998, we isolated B. holmesii from 32 nasopharyngeal specimens that had been submitted from patients suspected of having pertussis. Previously, B. holmesii had been associated mainly with septicemia and was not thought to be associated with respiratory illness. A study was undertaken to describe the characteristics of the B. holmesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…Both PFGE and multi‐locus sequence typing suggest that B. holmesii shows very little genetic diversity (Mazengia et al ., ; Diavatopoulos et al ., ). It is tempting to speculate that the low degree of diversity is the result of a population bottle neck caused by the invasion of a new nice, i.e.…”
Section: Patient Data and Clinical Symptomsmentioning
confidence: 99%
“…Both PFGE and multi‐locus sequence typing suggest that B. holmesii shows very little genetic diversity (Mazengia et al ., ; Diavatopoulos et al ., ). It is tempting to speculate that the low degree of diversity is the result of a population bottle neck caused by the invasion of a new nice, i.e.…”
Section: Patient Data and Clinical Symptomsmentioning
confidence: 99%
“…Further, Mazengia, et.al. reported that recovery of Bordetella holmseii was inhibited when grown on Bordet Gengou selective medium. 5 In patients with respiratory symptoms resembling whooping cough, routine specimen collection procedures, using antibiotic-containing transport medium for Bordetella pertussis recovery, would most likely not support growth and isolation of Bordetella holmseii.…”
Section: Discussionmentioning
confidence: 99%
“…Bordetella holmseii has been recognized as a rare opportunistic pathogen, primarily causing infection in immunocompromised patients, with only nineteen cases of infection reported in the literature from 1995 through 2000. 5 Bacteria that are encapsulated have a reputation and predilection for virulence and are seen especially in cases of sepsis; however, evidence of the presence of a capsule in B. holmseii has yet to be determined and its typical lack of fulminant progression also supports this theory. 6,7 Bordetella holmseii respiratory infections most often resolve spontaneously; other more serious infections, including bacteremia, septic arthritis, and endocarditis, generally have favorable outcomes with proper therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A differential detection of B. pertussis vs. B. holmesii is only possible using a discriminatory stem-loop probe in a PCR-based detection targeting IS481 (17). However, although reported in recent years (24), occurrence of B. holmesii infection in pertussis or pertussis-like syndrome is quite rare, and clinical significance of B. holmesii infection in the disease process is yet to be unequivocally established. The insertion sequence region IS481 is present in multiple copies (80-100) in B. pertussis genome (25), and, thus, can provide the increased sensitivity of an amplificationbased assay.…”
Section: Discussionmentioning
confidence: 99%